Endocrine system-related adverse events associated with PD-1/PD-L1 inhibitors: data mining from the FDA adverse event reporting system - Shi, Hongxia; He, Yunhua; Dan, Siyuan; Yang, Lin; Wang, Jing; Chen, Li; Chen, Zelian (Frontiers in Medicine, 2024)
Background: Various immune checkpoint inhibitors, such as programmed cell death protein-1 (PD-1) and its ligand (PD-L1), have been approved for use, but they have side effects on the endocrine glands. Methods: Adverse event reports related to PD-1/PD-L1 inhibitors from the FDA Adverse Event Reporting System (FAERS) from the first quarter of 2019 to the first quarter of 2023 were extracted, and the reported Odds ratio methods (ROR method) and comprehensive standard methods (MHRA methods) were used for data mining and analysis. Results: A total of 5322 reports （accounts for 6.68% of the total reports）of AEs in endocrine system were collected, including 1852 of pabolizumab（34.80%）, 2326 of navuliumab（43.71%）, 54 of cimipriliumab（1.01%）, 800 of atilizumab（15.03%）, 222 of duvariumab（4.17%） and 68 of averumab（1.28%）. Endocrine system-related AEs were mainly present in men (excluding those treated with pembrolizumab) aged ≥65 years. The ratio of AEs components in the endocrine system for the six drugs was approximately 3–8%. The main endocrine glands involved in AEs were the thyroid (pembrolizumab), pituitary and adrenal (nivolumab), adrenal (cemiplimab, atezolizumab, and avelumab), and thyroid (durvalumab). Most patients experienced AEs between 30 and 365 (mean, 117) days,the median time was 61d. AEs resulted in prolonged hospitalization in >40% and death in >10% of cases after administration of pembrolizumab, nivolumab, or durvalumab. Conclusions: Men aged ≥65 years should be concerned about endocrine-related AEs. There was a lengthy interval between the use of PD-1/PD-L1 inhibitors and endocrine system-related AEs, but the outcome was serious. Special attention should be given to endocrine system-related AEs when using pembrolizumab, nivolumab, or durvalumab.